Membangun Budaya Mencipta dan Kreativitas Kerja Karyawan pada Industri Kreatif di Provinsi Banten - Aan Khurosani (Performance: Jurnal Personalia, Financial, Operasional, Marketing dan Sistem Informasi, 2020)
Creative industry is a very potential sector in the development of small and medium industries in Indonesia. Creative industries are industries that focus on creating goods and services by relying on expertise, talent and creativity as intellectual property. The purpose of this study was to analyze the influence of creating culture, freedom of creation behavior and willingness to open a network of employee work creativity in the creative industries in Banten Province. The sampling technique uses purposive sampling technique with a sample of 95 respondents. Data analysis using Structural Equation Modeling analysis with PLS 3.0 program. The results showed that there was no influence of creating culture on employee work creativity. There is a positive and significant influence of creating culture on freedom of creative behavior, there is a positive and significant influence on freedom of creation behavior on employee work c[i]reativity, there is a positive and significant influence on creating freedom of behavior on the willingness to open networks and there is a positive influence on willingness to open networks on employee work creativity.